Dermanyssus gallinae (chicken mite): an underdiagnosed environmental infestation. (27th March 2013) - Collgros, H.; Iglesias‐Sancho, M.; Aldunce, M. J.; Expósito‐Serrano, V.; Fischer, C.; Lamas, N.; Umbert‐Millet, P.
Summary: Dermanyssus gallinae is a mite that normally parasitizes small birds but may occasionally bite humans. We report an unusual case of an 82‐year‐old woman who presented with pruritus and bite‐like lesions over her trunk. Other members of the household were also affected. On physical examination, mites < 1 mm in size were found on the patient's body. The family were residing in the city centre and had no pets, but there were pigeon nests in close proximity to the house. Most dermatologists have difficulties identifying ectoparasitosis. In the case of D. gallinae, the small size of the mites and the fact that they leave the host after feeding means that they may not be seen at presentation, thus such infestations are likely to be underdiagnosed. Physicians should be aware that infection with this mite is possible even in patients from urban areas, and it should be included in the differential diagnosis of conditions causing recurrent pruritus unresponsive to standard treatments.